2019
DOI: 10.1038/s41467-019-08966-9
|View full text |Cite
|
Sign up to set email alerts
|

Topologically enhanced harmonic generation in a nonlinear transmission line metamaterial

Abstract: Nonlinear transmission lines (NLTLs) are nonlinear electronic circuits used for parametric amplification and pulse generation, and it is known that left-handed NLTLs support enhanced harmonic generation while suppressing shock wave formation. We show experimentally that in a left-handed NLTL analogue of the Su-Schrieffer-Heeger (SSH) lattice, harmonic generation is greatly increased by the presence of a topological edge state. Previous studies of nonlinear SSH circuits focused on solitonic behaviours at the fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 55 publications
1
106
0
Order By: Relevance
“…In addition, the planar geometry and ultrathin thickness of the metasurface will facilitate its integration with existing electronic systems. This includes electronic topological insulators as well as PTIs based on lumped‐circuit components . Attractively, the addition of electrical elements to the proposed PCB‐compatible design would enable tunable/switchable topological states and reconfigurable pathways .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the planar geometry and ultrathin thickness of the metasurface will facilitate its integration with existing electronic systems. This includes electronic topological insulators as well as PTIs based on lumped‐circuit components . Attractively, the addition of electrical elements to the proposed PCB‐compatible design would enable tunable/switchable topological states and reconfigurable pathways .…”
Section: Resultsmentioning
confidence: 99%
“…The major challenge here is the difficulty in implementation of sizeable nonlinearities manifested already at the two-photon level [16]. To overcome this difficulty and to bridge the gap between quantum-optical topological states and physics of interacting systems, we adopt the concept of topolectrical circuits [17,18,19,20,21,22] applying them to emulate an interacting two-body problem in one dimension. As detailed below, this approach is based on mathematically rigorous mapping of quantum two-body problem onto the classical setup of higher dimensionality, and this correspondence renders the topolectrical platform a powerful tool to study topological states of interacting photons.…”
mentioning
confidence: 99%
“…Indeed, it has been shown that when a photonic topological insulator is embedded in an optical medium with Kerr nonlinearity, lattice edge solitons could arise [13,14]. The possibility to enhance the conversion efficiency of harmonic generation in the presence of topological edge states has also been studied [15,16]. Moreover, traveling-wave amplifiers [17], topological sources of quan-arXiv:1907.00444v1 [physics.optics]…”
mentioning
confidence: 99%